DETERMINATION OF DEPRESSION AND ANXIETY AMONG MEDICAL UNIVERSITY OF LARKANA - SHAIKH , B; JISKANI , SA; PRITHIANI , SL; ABBASI , A; MUGHERI , FP; SIRAJ , A; ISRAN , B; SHAIKH , M; SALEEM , R; UNDER , K; et al. (Biological and Clinical Sciences Research Journal, 2023)
A stressful environment is concerned with medical colleges, and often, they have an adverse effect on physical health, academic performance, and psychological wellness. There is a high percentage of anxiety and depression in the medical curricula, and still, it is unfortunate to see the faces behind the white coats. The study aimed to determine the prevalence of depression and anxiety among medical students at Shaheed Mohtarma Benazir Bhutto Medical University Larkana. The research was conducted from March to June 2023 and included all medical students who had spent at least six months in SMBBMU Larkana and had no physical illness. The results were analyzed using percentages and proportions through SPSS 24. The study found a high incidence of depression and anxiety in medical students, which can negatively affect their learning, productivity, and quality of life, as well as the care of patients. The research highlights the need for proper intervention and early detection measures to reduce the effects of depression in education and career.